Tricyclohexyl{2- (3,5-di-tert-butyl-4-hydroxybenzyl)sulfanyl acetato-kap pa O} tin(IV) - Lee, S.M.; Lo, K.M.; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
The title compound, [Sn(C6H11)3(C17H25O3S)], exists as a monomeric molecule with the SnIV atom in a distorted tetrahedral C3O coordination geometry. The presence of two bulky tert-butyl groups on the carboxylate prevents any hydrogen-bonding interactions involving the hydroxy group.